Leashing Chinese AI Needs Smart Chip Controls. - Chan, Kyle; Wang, Ray (Foreign Policy)
The article focuses on the challenges faced by China's artificial intelligence (AI) sector due to limited access to advanced computing power, primarily driven by U.S. export controls on semiconductors. While China has made significant strides in AI development, it lags behind the U.S. in compute capacity, with Chinese firms like Tencent and Baidu highlighting compute constraints as a major bottleneck. Despite efforts to utilize domestically produced AI chips from Huawei, many Chinese tech companies prefer Nvidia chips due to superior performance and established software ecosystems, complicating the transition to local alternatives. The article suggests that U.S. export policies should be carefully calibrated to maintain a competitive edge while preventing a shift towards reliance on Chinese chipmakers.